UPAYA MENGGALI POTENSI DUSUN SEMAYA MELALUI ANALISIS KEBUDAYAAN - Dian Bayu Firmansyah; Eko Kurniawan; Hartati Hartati; Heri Widodo; Diana Puspitasari; Haryono Haryono; Yudi Suryadi; Anggita Stovia; Muammar Kadafi (LPPM Universitas Bina Bangsa, 2022)
This community service activity aims to explore the potential of both Human Resources and Natural Resources in Semaya Hamlet, considering the geographical condition of Semaya Hamlet bordering the protected forest area causing Semaya area as separated from urban civilization. Semaya is one of the hamlets in Sunyalangu Village, Karanglewas-Banyumas located under the slopes of Mount Slamet with a distance of about 18 km from the center of Purwokerto. The location of Semaya Hamlet is slightly isolated both in terms of location and government touch in development so that the economic level of the community is relatively low. Therefore, in this devotional activity, there are 3 (pieces) of main activities consisting of: SWOT analysis of 7 (seven) aspects of its culture, mapping and documenting village data, profiling hamlets, and creating learning content